Effect of simultaneous pancreas-kidney transplantation on blood glucose level for patients with end-stage renal disease with type 1 and type 2 diabetes - Liu, Luhao (Ann Transl Med, 2019)
BACKGROUND: Simultaneous pancreas-kidney (SPK) transplants for patients with type 1 diabetes mellitus (T1DM) remains disproportionately higher than that for type 2 diabetes mellitus (T2DM) patients. However, understanding the surgical outcomes for these patients is not well described. Therefore, the results of DM patients with end-stage renal disease and their transplantations were reported. METHODS: Between September 2016 and June 2019, 63 SPK transplants were performed in our organ transplantation center. χ(2) and t-test compared the variables between the groups and the record review verified the patient survival. Using Kaplan-Meier survival estimates and Cox proportional hazards regression, we examined the influence of SPK on patient and graft survivals. RESULTS: Sixty-three SPK transplantation was performed, 18 (29%) were T1DM, and 45 (71%) T2DM. T2DM recipients had older age, duration of diabetes, and pretransplant dialysis time. No differences were found in human leukocyte antigen (HLA) mismatch, body mass index (BMI), and other variables. Patient survivals for T1DM was 98.2% and 94.8% at 1 and 2 years vs. 100% and 94.1% for T2DM recipients (P=0.87). There was no increased risk between kidney disease, pancreas failure, or death when comparing T2DM and T1DM. CONCLUSIONS: In our single-center cohort of SPK transplants, we concluded that SPK recipients with T2DM diagnosis were not at increased risk for death, kidney failure, or pancreas failure when compared with recipients with T1DM.